AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARY - Meita Lesmiaty Khasyar; Novia Anggraeni (JELLi Journal, 2020)
Vocabulary is an essential building block of language and as such it makes sense to be able to measure learners’ knowledge of it. The objectives of the research was to know the difficulties faced by students in learning vocabulary and what the factors that cause students’ difficulties in learning vocabulary. The number of participants who selected by the writer are 10 eighth grade students of SMP Pesona Dywantara using purposive sampling. The research design used in this research was descriptive qualitative because this research results the descriptive data in the form of written or picture data from the subjects of the research being observed. Based on the data analysis, the writer found three difficulties faced by students. Those are; spelling and pronunciation, words meaning and using words appropriately. Furthermore, the difficulties caused by many factors. Such as, related to their frequency of study, unfamiliar with English vocabulary and limitation of their vocabulary